Sistem Pakar Untuk Mendiagnosa Kerusakan Hardware Laptop Menggunakan Metode Certainty Factor - Romadhoni, Rahma Melyana; Zayn, Afta Ramadhan (Al-Mantiq, 2023)
Currently the development of information technology is increasingly sophisticated and increasing. All fields ineveryday life can not be separated from technology, especially laptops. Almost all fields use a laptop to get work done. This can cause problems when using a laptop, namely if one of the devices / components suffered damage. When these problems arise, sometimes ordinary users did not understand and had to take it to a technician, where the workmanship and cost was more expensive. Not that’s all, access to the laptop service is quite far which will take time and a fairly long time, only for problems that should be solved on their own. For simplify and speed up the solution, we need and application that can provide solutions that are precise, accurate and efficient. An expert system is a system that harnessing human-to-computer knowledge. One of the methods used in expert system is the certainty factor method, where this method helps overcome the problem of uncertainty, and know the level of user confidence in the problem at hand. Based on the research results, the results of program testing carried out with experts, and this has an accuracy rate of 90% on 10 types of damage tested.